New Caenidae (Insecta, Ephemeroptera) from Far East Russia - Tiunova, Т.M. (Вестник зоологии, 1999)
Caenis pustula sp. n. is described from the larvae and reared male imago. Previously unknown males and females of Caenis miliaria (Tshernova) and Caenis maculata (Tshernova) are described and illustrated, and larvae of the seven species are redcscribed and illustrated. Complementary data on the distribution of C. amurensis Kluge are presented.